Diallyl trisulfide protects against high glucose-induced cardiac apoptosis by stimulating the production of cystathionine gamma-lyase-derived hydrogen sulfide. (15th September 2015) - Tsai, Cheng-Yen; Wen, Su-Ying; Shibu, Marthandam Asokan; Yang, Yao-Chih; Peng, Hanjing; Wang, Binghe; Wei, Yu-Min; Chang, Hung-Yu; Lee, Cheng-Yu; Huang, Chih-Yang; Kuo, Wei-Wen
Abstract: Background: Cystathionine-γ-lyase (CSE)-derived hydrogen sulfide (H2S) is a potent cardioprotective agent. We investigated the effects of diallyl trisulfide (DATS) on CSE expression and H2S generation in myocardium and examined whether DATS-mediated H2S generation effectively protects rat heart from diabetes-induced cardiac damage. Methods: The correlations between the effects of hyperglycemia and diabetes on CSE expression and the effects of DATS and H2S on hyperglycemia and diabetes were examined in vitro in the cardiomyocyte cell line H9c2 and in vivo in hearts from rats with streptozotocin-induced diabetes mellitus (DM). Results: Expression of CSE, a catalyst of H2S production, was suppressed in H9c2 cells treated with high glucose (33 mM) and in DM rat hearts. CSE suppression also correlated with a decrease in the activation of the pro-survival protein kinase Akt. Treatment of H9c2 cells with DATS resulted in increased CSE expression and a reduction in apoptosis via a mechanism involving IGF1R/pAkt signaling and by modulating the expression of reactive oxygen species-related enzymes. The role CSE plays in the cardioprotective effects of DATS was further confirmed by CSE inhibition assays including inhibitors and siRNA. Conclusion: DATS produces H2S as efficiently as NaSH and DATS-derived H2S provides effective cardioprotection. Further, our data indicate that H2S plays a major role in the protective effect of DATS against apoptosis of cardiomyocytes.